Pre-shipment inspection as a control system for the importation of inputs from China, from the metal- mechanical sector in Lima 2010-2015 - Aguilar Lugo, Yesenia (2018)
Objective: To determine the extent to which the pre-shipment inspection control system benefits the management of imported inputs from China for companies in the metal-mechanic sector in Lima 2010-2015. Method: Descriptive, correlational, and of non-experimental - transverse type. The subjects or objects of study, are the set of companies in the metal-mechanic sector of Metropolitan Lima. The conclusions of this investigation will be valid for companies in the metal-mechanic sector of Peru. Results: The research was carried out in the metal-mechanic sector of Lima. The general hypothesis with its corresponding specific hypotheses has been tested, that is to say that the pre-shipment inspection control system significantly benefits the import management of inputs from China for companies of the metal-mechanic sector in Lima 2010-2015. Conclusions: Of the 18 companies that have been researched 94% of respondents believe that the pre-shipment inspection control system significantly benefits the import management of inputs from China for companies in the metal-mechanic sector of Lima.